(3GdJMaI GdXQjaI ef cd fcJI dWjaIs
(3ChdgG (B:s
(3eHJhQ(B( (3fGbU GdebOeI(B) (3hjHOC HGdHGH GdChd ai fhGOQ GdYQH , Hbhdg (B: (3bjd Ef eYf Hf RGFOI cGf ai UjOg aQCi TjNG ef GdYQH ebHdG ef GdHQjO Ydi eYf hSde Ydjg , hbGd dg (B: (3ef Cjf hEdi Cjf ? bGd (B: (3LFJ HbKGA HZjQ ChGfgG s
(3BNQgG (B:s
(3cd ef MaQ dCNjI MaQI jbY ajgG , hcd ef Jdce cdGeG YGO Ydjg , hEf cGf NjQG eOM ajg , hEf cGf TQkG hbY ajg ef dG jMaX dSGfg JbY efg NWjFGJg hjTeJ Hg ENhGfg hLjQGfg hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH GdCeKGd , hGdMeO ddg Ydi cd MGd s
(3hbO cJHJ HCSdhH OGQL McGjGJ hCTYGQ ai NeS hQbGJs
(3hgh eQJH Ydi NeSI YTQ HGHkG ceG ai agQSJ GdfSNI GdKGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B144 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs